High pressure growth and electron transport properties of superconducting SmFeAsO1−xHx single crystals. Issue 3 (1st September 2017) - Iimura, Soshi; Muramoto, Takashi; Fujitsu, Satoru; Matsuishi, Satoru; Hosono, Hideo
Abstract: We report the single crystal growth and characterization of the highest T c iron-based superconductor SmFeAsO1− x H x . Some sub-millimeter-sized crystals were grown using the mixture flux of Na3 As + 3NaH + As at 3.0 GPa and 1473 K. The chemical composition analyses confirmed 10% substitution of hydrogen for the oxygen site ( x  = 0.10), however, the structural analyses suggested that the obtained crystal forms a multi-domain structure. By using the FIB technique we fabricated the single domain SmFeAsO0.9 H0.10 crystal with the T c of 42 K, and revealed the metallic conduction in in-plane ( ρ ab ), while semiconducting in the out-of-plane ( ρ c ). From the in-plane Hall coefficient measurements, we confirmed that the dominant carrier of SmFeAsO0.9 H0.10 crystal is an electron, and the hydride ion occupied at the site of the oxygen ion effectively supplies a carrier electron per iron following the equation: O 2−  → H −  +  e − .